A influência das condições termo-pluviométricas nos indicadores do comércio de Maringá, Estado do Paraná: um ensaio metodológico na perspectiva da valoração ambiental - Andriucci, Lays Regina [UNESP]; Sant'Anna Neto, Joao Lima [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2007)
This article analyzes the degree of thermopluviometric influence on certain indicators in the commerce of Maringa, state of Parana. To the end, climate elements, such as the temperature and prectipitation as well as certain economic indicators, namely: ICMS (taxes), SCPC, Video-Check, Consumption and Consumers of Electric Energy were studied. Graphical analyses along with statistical applications of correlation and regression were performed, as well as the examination of a case study. It is believed that the groups investigated showed variations in the forms of correlation. The results herein presented are in the manner of preliminary trial, representing a first attempt at measuring the actual relationship between the climatic variables (temperature and precipitation) with certain behavioural indicators of commerce in the city of Maringa.
The influence of thermopluviometric conditions in the commerce indicators of Maringa city, state of Parana: a methodological essay in the environmental valoration perspective.
Keywords: climate; temperature; precipitation; economy; indicators; Maringa